การประยุกต์วิธีธรณีสถิติในการพยากรณ์อัตรามรณะไทย - นิติมา เพชรชนะ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
This research aims to forecast the mortality rates of Thai population in the next 10 years by using 4 models: Lee-Carter Model Lee-Carter Model with Geostatistical techniques Median polish Model and Median polish Model with Geostatistical techniques. In addition to comparing the estimated mortality rates from 4 models to find the model is most appropriate by using mean absolute percentage error (MAPE). The results show that the Lee-carter Model with Geostatistical techniques gives the lowest average MAPE for both male and female, which are 0.0026% and 0.0017%, respectively. The four models generate different values of the mortality rates but similar trend. For people aged under 80 years, the mortality rates tend to decrease over time. While people aged over 80 years, the mortality rates tend to increase over time. By applying the Bootstrap methodology to the Lee-Carter model with Geostatistical techniques in years 2012, 2013, 2016, 2019, and 2022, they reveal that the life expectancy of females is higher than that of males in all ages in those years. The life expectancy at age 60 are 19.12 years for males and 22.25 years for females in year 2016. The life expectancy has an increasing trend over time.